Off Duty Dilemma: A quantative study into the quality of first aid training in nurse education - Spiers, Jessica (2011)
This study discusses first aid and its incorporation into nurse education. There is a significantly bias argument presented throughout literature which suggests that nurses should be equipped with the skills to deal with an injured person in a pre-hospital situation. This appears not to be the case in reality, with research suggesting that there are many registered nurses practicing poor techniques in first aid. There has been no research into the first aid knowledge of final year student nurses, hence the rationale for this study. This quantitative research used structured questionnaires to generate data. 200 final year students were approached, resulting in 141 students completing the questionnaire. 52 students were from the Masters of Nursing Science course, 51 from the diploma pathway and 38 from the degree pathway. The raw data was coded and entered into SPSS (Statistical Package for the Social Sciences) for statistical analysis; where the patterns and trends became identifiable. Results were split into first aid knowledge and legal and professional implication awareness. The study generated particularly polarised results, with the consensus matching the supporting literature. Many students believe first aid to be part of their role; however, there is a clear indication for the need to increase the amount of training before this becomes reality. Alarmingly, there is evidence of unrealistic levels of confidence amongst student nurses that may put them at risk of legal consequences, especially with almost half the sample population not having insurance. The results did show that first aid knowledge correlates to academic level. The voice of student nurses should be considered when planning the curriculum, and when they identify new skills and role adaptations they want to fulfil, their opinions should be embraced. First aid training could potentially increase the positive reputation of nurses further whilst improving patient safety.